Pembentukan Karakter Berbasis Pendidikan Pesantren: Studi tentang Ragam Nilai dan Metode Pembelajaran - Andrianto Andrianto; Sumiarti Sumiarti; Nofitayanti Nofitayanti; Rully Hidayatullah (Prodi PAI STAI Sumatera Medan, 2022)
Education at the Miftahul Istiqomah Sungai Asam Islamic boarding school until now still tends to use traditional educational methods in its learning, this is maintained in order to continue to use the procedures taught by its predecessors. Apart from using traditional educational methods, this Islamic boarding school still carries out learning also at night, in contrast to learning that is implemented by schools in general during the day. On the basis of these problems, the purpose of this study is to analyze the variety of values ​​and traditional learning methods used in the Miftahul Istiqomah Sungai Asam Islamic boarding school. The method used in this study is descriptive qualitative with data collection techniques namely observation, wawancaras and documentation. The results of this study explain that the character values ​​of the students developed through Islamic boarding school education, namely the character values ​​in relation to God, the character values ​​in relation to oneself, and the character values ​​in relation to the environment. Then the traditional learning methods that are always used by educators for their students, namely the halaqah method, the sorogan method, the habituation method and the exemplary method.